2005
DOI: 10.1002/ppul.20334
|View full text |Cite
|
Sign up to set email alerts
|

Adenotonsillectomy for Obstructive Sleep Apnea in Children with Prader‐Willi Syndrome

Abstract: Summary. The aim of our study was to evaluate the efficacy of adenotonsillectomy for the treatment of obstructive sleep apnea syndrome (OSA) in pediatric patients with Prader-Willi syndrome (PWS), and to describe the postoperative complications. Five patients (4 males; median age, 4.4 years; range, 1.6-14.2 years) were studied. All patients underwent an overnight cardiorespiratory sleep study. All patients had adenotonsillar hypertrophy (ATH), and two were also obese. The preoperative obstructive apnea/hypopne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 24 publications
2
58
0
Order By: Relevance
“…In addition, they found that hypercapnic ventilator responses in patients with PWS showed lower increments of ventilation than was found among their peers, thus supporting the previous claim of abnormal peripheral chemoreceptor function in PWS. 18,24 Our study complements the findings of Pavone et al 25 in their review of 5 children with PWS who underwent T&A. In that report, 1 child who initially had moderate OSA normalized after surgery; 3 patients with severe OSA and 1 patient with moderate OSA by AHI score improved to mild OSA.…”
Section: Commentsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, they found that hypercapnic ventilator responses in patients with PWS showed lower increments of ventilation than was found among their peers, thus supporting the previous claim of abnormal peripheral chemoreceptor function in PWS. 18,24 Our study complements the findings of Pavone et al 25 in their review of 5 children with PWS who underwent T&A. In that report, 1 child who initially had moderate OSA normalized after surgery; 3 patients with severe OSA and 1 patient with moderate OSA by AHI score improved to mild OSA.…”
Section: Commentsupporting
confidence: 75%
“…Our study also adds useful information about a younger age group. Pavone et al 25 studied children with a me- dian age of 4.5 years (youngest age, 1.9 years). The patients in our study had a median age of 3 years, and the youngest patient was only 6 months old.…”
Section: Commentmentioning
confidence: 99%
“…It was seen that the children with Prader-Willi syndrome that have hypotonia and obesity along with facial anatomical abnormalities benefited from adenotonsillectomy in the presence of adenotonsillar hypertrophy; but postoperative complications increased in patients especially under 3 years of age (10). As in our patient, improvement can be achieved especially in swallowing in the presence of adenotonsillar hypertrophy through adenotonsillectomy in children with a disease such as cerebral palsy, which has an abnormal motor tone.…”
Section: Discussionsupporting
confidence: 52%
“…This emphasizes that PWS is per se a condition with a high mortality risk which requires careful clinical management with or without GH treatment. We do not advise adenoidectomy and tonsillectomy on every child with PWS, as firstly the surgery may be dangerous [Pavone et al, 2006] and when needed, it must be performed with cardiac and respiratory monitoring for a 24-hr period. Furthermore treatment could worsen speech problems (personal experience) and it sometimes has no effect on sleep obstructive apnea [Festen et al, 2006].…”
Section: Discussionmentioning
confidence: 98%